Dietary Monounsaturated Fatty Acids Intake and Risk of Skin Photoaging - Latreille, Julie (Public Library of Science, 2012)
BACKGROUND: Intake of monounsaturated fatty acids has been reported to reduce oxidative stress, insulin resistance and related inflammatory processes and may thus protect from skin photoaging. The objective of this study was to investigate the association between the risk of photoaging, monounsaturated fatty acids intake and the sources of monounsaturated fatty acids. METHODOLOGY/PRINCIPAL FINDINGS: A cross sectional study was conducted within the framework of the SUVIMAX cohort. The survey included 1264 women and 1655 men aged between 45 and 60 years old. Dietary monounsaturated fatty acids intakes were estimated by dietary source through at least ten 24-h diet records completed during the first 2.5 years of the follow-up period. Severity of facial skin photoaging was graded by trained investigators at baseline during a clinical examination using a 6-grade scale illustrated by photographs. A lower risk of severe photoaging was associated with higher intakes of monounsaturated fatty acids from olive oil in both sexes. Strikingly, no association was found with intake of monounsaturated fatty acids from animal sources whether from dairy products, meat or processed meat. CONCLUSION/SIGNIFICANCE: These findings support the beneficial effect of dietary olive oil or healthy diet habits associated with olive oil consumption on the severity of facial photoaging.